A desjudicialização da prova e seus reflexos no processo civil - Miranda, Lygia Helena Fonseca Bortoluci (2024)
The aim of this paper is to encourage debate to reduce judicial intervention in the production of evidence in Brazil, in order to demonstrate how the extrajudicial production of evidence by the parties can function as an intelligent mechanism to make the judicial process more dynamic and efficient, as well as acting as an instrument to enhance the fundamental right to evidence, given that the instructional phase in court, in most cases, consumes significant time in the process and the energy of the parties. Taking as a premise the basic principles that guide the institution of evidence in Brazilian law, notably the principles of atypicality, cooperation and adversarial proceedings, it was found that, strictly speaking, there is no incompatibility between the Brazilian legal system and the proposal to reduce judicial intervention in the production of evidence. Throughout the work, we have identified practical examples that demonstrate that the 2015 Code of Civil Procedure already includes in its text various situations in which it admits evidence produced outside the judicial system, which often acts as a legitimizing factor for the party's own interest in taking legal action. Based on these findings and with a view to encouraging legal practitioners to open up to this possibility of evidence being produced by the parties, before or in the course of legal proceedings and without the supervision of the magistrate, it was shown that procedural legal deals are the key to systematizing evidence production in an extrajudicial environment. The advantages of out-of-court production compared to the action for the early production of evidence provided for in article 381 of the CPC were also approached. We worked on the possible procedural and substantive challenges that tend to be faced by legal practitioners if this new model of evidentiary production is implemented by Brazilian procedural legislation. Finally, we presented a proposal for systematizing the production of oral, expert, document exhibition and electronic documentary evidence by the parties out of court